FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN PENDENGARAN PADA PEKERJA DIBAGIAN PRODUKSI DI PT. HERVENIA KAMPAR LESTARI - Lira Mufti Azzahri; Riri Indriani Indriani (Universitas Pahlawan, 2019)
Every exposed worker needs to improve hearing. Several factors cause hearing complaints when exposure factors, duration of exposure, and the use of APT (Ear Protection Equipment). The purpose of this study was to study any factors related to hearing workers at PT. Hervenia Kampar Lestari. Quantitative research design with Cross Sectional design, this study was conducted in July 2019 at PT. Hervenia Kampar Lestari. The population in this study were production workers who studied 120 people. The sample technique used is simple random sampling with a total sample of 92 respondents. Data obtained were analyzed by Chi Square test, the significance level was 95%. Based on the results of research that shows there is a significant relationship between agreement with hearing this is evidenced by the value of p (0,000)